Security analysis of public cloud computing. (1st January 2012) - Idziorek, Joseph; Tannian, Mark
Cloud computing is in its infancy and continues to evolve. As this evolution proceeds, there are a number of privacy and security concerns emerging from the cloud computing model that need to be addressed before broad acceptance occurs. This paper is an initial literature survey of cloud computing security, which promises to be a challenging research area. Although cloud computing security research inherits previous research from its elemental technologies, this paper will limit its focus on surveying cloud computing targeted research. By performing a systematic analysis of the security aspects of the cloud model, this work seeks to succinctly clarify why security continues to be a significant impediment for cloud adoption.